An investigation on plant species composition and diversity in the coniferous and broadleaved plantations: Case study of Bibi Yanlu Forest Park, Astara, Iran - TOWHID SALAHI; HASSAN POURBABAEI; MAZIAR SALAHI; SARKHOSH KARAMZADEH (Society for Indonesian Biodiversity, 2017)
Salahi T, Pourbabaei H, Salahi M, Karamzadeh S. 2017. An investigation on plant species composition and diversity in the coniferous and broadleaved plantations: Case study of Bibi Yanlu Forest Park, Astara, Iran. Biodiversitas 18: 958-963. The aim of this study was to investigate vegetation composition in hardwood and coniferous plantations in 220 ha of Loblolly pine (Pinus taeda L.), Caucasian alder (Alnus subcordata C.A.Mey) and poplar (Populus deltoids) and its comparison with natural forests in Bibi Yanlu protected forest park in Astara, north of Guilan Province, Iran. Totally, 60 sampling plots of 1000 m2 by systematic-random method using 150 × 150 m grid in plantation and 200 × 200 m in the natural forest were established. To study the biodiversity, Shannon-Wiener, Simpson's diversity indices, Hill evenness and richness indices were utilized. The results of this research showed that there is a significant difference for diversity and richness indices between natural forest and plantations. Diversity and richness indices in the natural forest were higher than Loblolly pine, poplar and alder plantations. The Hill evenness index between natural forest and plantations did not indicate significant differences. In terms of herbaceous and woody species similarity, alder plantation was closer to natural forest, and pine plantation had the least similarity with the natural forest.